Dual biocontrol and osmotic stress mitigation by endophytic Aspergillus micronesiensis and Penicillium momoi against fusarium pathogens - Ali Aligholizadeh; Mina Salehi; Seyed Bagher Mahmoudi; Naser Safaie (PLoS ONE, 2026)
Global challenges associated with crop diseases and abiotic stress necessitate sustainable agricultural solutions. This study investigated the biocontrol and osmotic-stress mitigation potential of two endophytic fungi, which were isolated from native plants and subsequently identified as Aspergillus micronesiensis and Penicillium momoi . Their antagonistic activities against Fusarium oxysporum f. sp. lycopersici (FOL), F. oxysporum f. sp. radicis-lycopersici (FORL), and F. pseudograminearum (FPS) were evaluated. Complementary antagonistic mechanisms were observed: P. momoi primarily inhibited pathogen growth through direct mycelial competition, while A. micronesiensis predominantly exerted effects through antibiosis. In dual-culture assays, A. micronesiensis inhibited FOL, FORL, and FPS by 39.05%, 39.93%, and 54.59%, respectively, whereas P. momoi caused inhibition rates of 51.84%, 64.74%, and 60.66%, respectively, demonstrating strong biocontrol potential. The salt tolerance assay revealed that both endophytes were able to grow on media containing up to 3 M NaCl. Although, optimal growth for both isolates occurred at 1 M NaCl, A. micronesiensis showed a greater increase in growth relative to the control (2.06 times). In contrast, P. momoi maintained more consistent growth across the 0–1 M NaCl range. However, growth of both isolates declined at higher salt concentrations. The developed wettable powder formulation maintained high spore viability for at least 27 months under room-temperature conditions. This research highlights A. micronesiensis and P. momoi as promising agents for managing Fusarium diseases and enhancing plant salinity tolerance. Further metabolomics investigations are recommended to clarify the functional roles of these endophytes in crop protection under stress conditions.